Literature Review. The acceptability of Moringa Leaf (Moringa Oleifera) enriched foods in Indonesia - Anisa Nur Rohman; Setyaningrum Rahmawaty (AcTion: Aceh Nutrition Journal, 2024)
Moringa leaves (Moringa oleifera) have many health benefits and have been used by the wider community to support health. The purpose of this review is to provide an overview of the acceptability of food products substituted with moringa leaves, based on studies conducted in Indonesia. Indosesia’s reference database, Garuda (Garba Rujukan Digital), was used for the eligible studies. The search terms used to obtain relevant studies were "Moringa leaf," "organoleptic," and "acceptability" published between 2016 and 2021. The inclusion criteria were full-text articles written in Indonesian or English and published in Sinta 1-4 indexed journals. This study used a completely randomized design and sensory testing in humans. Results: Nine studies qualified for this review, with a variation substitution of moringa leaf in instant noodles, jelly candy, cookies, biscuits, and pancakes. The addition of moringa leaves to the products was carried out in the form of powder, protein concentrate, flour, and puree–1,5-5% to improve the content of certain nutrients, such as protein, beta-carotene, iron, calcium, vitamin C, or overall nutrients. Untrained panelists of 15-33 were used to select consumer preferences for the products, followed by nutrient analysis to determine the increase in the content of certain nutrients by adding moringa leaves. In conclusion, the more moringa leaves were added to the food products, the lower the panelists' preference for aroma, color, texture, and taste.